Analysis On Subtitling Equivalence In Harry Potter And The Deathly Hallows Part 2 Movie - Wardhana, Gunawan Eko (2012)
The aims of this study are to describe the equivalent strategies used in subtitling of Harry Potter and the Deathly Hallows Part 2 Movie and to know the equivalence and non equivalence of subtitling of Harry Potter and the Deathly Hallows Part 2 Movie with the target language The writer employs descriptive qualitative method. By this method, the writer uses the subtitling of Harry Potter and the Deathly Hallows Part 2 movie as the source data, and the data are word, phrase, clause, and sentence of subtitling. The writer uses documentation technique in collecting the data. The collected data are analyzed by comparison method. The results of this research paper show that first, the writer finds that there are 8 types of equivalent strategy found in the movie, namely; (1) addition consisting 120 data or 23. 90 %, (2) deletion consisting 223 data or 44. 42 %, (3) adoption consisting 55 data or 10. 95 %, (4) adaptation consisting 23 data or 4. 58 %, (5) category shift consisting 22 data or 4. 38 %, (6) structural shift consisting 9 data or 1. 79 %, (7) level shift consisting 41 data or 8. 16 %, (8) intra-system shift consisting 9 data or 1. 79 % . The second, the writer finds that from 843 data, there are 840 data or 99. 64 % belong to equivalent subtiling and 3 data or 0. 35 % belong to non equivalent subtitling. So, the translation of subtitling Harry Potter and the Deathly Hallows Part 2 movie is good.